2022
DOI: 10.1093/plphys/kiac298
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional networks regulating suberin and lignin in endodermis link development and ABA response

Abstract: Vascular tissues are surrounded by an apoplastic barrier formed of endodermis that is vital for selective absorption of water and nutrients. Lignification and suberization of endodermal cell walls are fundamental processes in establishing the apoplastic barrier. Endodermal suberization in Arabidopsis (Arabidopsis thaliana) roots is presumed to be the integration of developmental regulation and stress responses. In root endodermis, the suberization level is enhanced when the casparian strip, the lignified struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
2
22
1
Order By: Relevance
“…Several copies of the well-known MYB4 phenylpropanoid biosynthesis regulator displayed an enhanced expression under MdMYB68 overexpression reaching 130.29-fold increase in expression ( Jin et al., 2000 ; Andersen et al., 2021 ). Finally, a MYB84-like transcription factor, which have been recently associated with the root suberization, is also highly induced ( Xu et al., 2022a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several copies of the well-known MYB4 phenylpropanoid biosynthesis regulator displayed an enhanced expression under MdMYB68 overexpression reaching 130.29-fold increase in expression ( Jin et al., 2000 ; Andersen et al., 2021 ). Finally, a MYB84-like transcription factor, which have been recently associated with the root suberization, is also highly induced ( Xu et al., 2022a ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven days after infiltration, Nicotiana benthamiana leaf samples were collected and washed with phosphate buffer twice for 10 min, then dehydrated in a graded series of ethanol and resin embedded as described previously ( Xu et al., 2022a ). For immuno‐localization, sections (10µm) of tobacco leaves were processed as described in ( Behr et al., 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative expression of eight genes related to apoplastic barriers in roots were investigated by qRT-PCR. Among them, four each that were respectively associated with CS formation and suberin monomer synthesis comprised MYB36, SHR1 (also regulates root suberization), PER64, and CASP (Naseer et al, 2012;Hosmani et al, 2013;Kamiya et al, 2015;Wang et al, 2020b;Wang et al, 2022a;Xu et al, 2022), and MYB41, CYP86A1, KCS20, and FAR1 (Höfer et al, 2008;Lee et al, 2009;Domergue et al, 2010;Kosma et al, 2014;Shukla et al, 2021). Osmotic stress increased the expression of PER64 in DS (24 h), downregulated that of MYB36, SHR1, and CASP to varying degrees in DS, and only slightly affected that of the four genes related to CS formation in DT (Figures 7A-D).…”
Section: Expression Of Genes Associated With Apoplastic Barriersmentioning
confidence: 99%
“…Interestingly, these mechanisms do not exist independently. A recent study from the perspective of root development in response to abiotic stress revealed that MYB36 balances root lignification and suberization by mediating the MYB74-MYB36-MYB92-MYB93 subnetwork ( Xu et al, 2022 ). The above studies indicate that the functions of MYB transcription factors are diversified, gradually forming a complex network mechanism.…”
Section: Introductionmentioning
confidence: 99%